(untitled) (Research, Society and Development, 2021)
The objective of this work was to evaluate the perception of students and teachers about agroecology in schools in the urban and rural areas of the municipality of Breves, archipelago of Marajó, Pará. The study was carried out in elementary schools, between January and February 2020. An exploratory descriptive research was used, through the application of questionnaires, for 94 students of the 9th grade and 16 teachers in the disciplines of geography and science. The data were analyzed in a spreadsheet manager and presented in graph format. The results obtained reveal that the majority (60%) and (75%) of the students are male, aged between 14-15 and 16-17 years, both in urban and rural areas, respectively. The most common form of access to the topic by these students has been via television and when approached in the classroom, most of the time, through the blackboard. Most teachers who work in the studied municipality have heard about agroecology either on television or in an academic environment. However, teachers in the urban area debate this theme sporadically in their classes, while those in the rural area make debates related to the agroecological theme whenever possible in class. Thus, rural students have greater knowledge about agroecology. On the other hand, it is observed that there is little dissemination of the agroecological theme in schools. We suggest pedagogical activities in elementary schools with the theme of agroecology, in order to strengthen teaching and learning.